Safety Chart for the Identification of Stability of Internal Dragline Dumps - Bharati A.K.; Ray A.; Rai R.; Shrivastava B.K. (My University, 2025)
Overburden dump is an integral part of opencast coal mining, and its stability is essential for the safe and economic extraction of the material. This paper discusses the stability analysis of internal dragline dump in dry condition using Monte Carlo simulation. A sensitivity analysis was performed to identify the most critical geometrical parameters—coal-rib height, slope angle and height of the bench between the coal-rib roof and dragline sitting level—considering the variability of geometrical parameters of the internal dragline dump. The probabilistic analysis of the dragline dump was conducted using various combinations of obtained critical parameters with the help of finite element method-based software RS2 (Version 9.0). By using the simulation results, a safety chart is proposed to estimate the stability of internal dragline dump in opencast operations, which is categorized into three zones; fail, vulnerable and safe. Each zone defines the amount of risk associated with a particular dump slope profile. The safety chart is validated from the previous research works, and the stability conditions of the internal dragline dumps are found similar in the safety chart. © 2020, The Institution of Engineers (India).